015 Identifying the cause of phenotypic variability in a family with non-dystrophic myotonia. Issue 3 (9th February 2012) - Raja Rayan, D; Haworth, A; Sud, R; McCall, S; Tan, S V; Durran, S; Davis, M; Hanna, M G
Abstract : Non-dystrophic Myotonia (NDM) is the commonest group of skeletal muscle channelopathies often causing severe myotonia in patients. It is either caused by mutations in the skeletal muscle chloride channel gene, CLCN1, or the sodium channel gene, SCN4A resulting in increased membrane excitability. An important unexplained issue in NDM is the significant phenotypic variability seen between patients with the same mutation and even within the same pedigree. We investigated the cause of this phenotypic variability in a pedigree where one branch of the family had several severely affected individuals, whereas those in another branch were more mildly affected. We tested the genes known to be associated with myotonia in both the severely and mildly affected individuals in this pedigree. Sequencing of the sodium channel gene, SCN4A, revealed that all affected individuals carried the known mutation c.3917G>T; p.Gly1306Val, consistent with a diagnosis of Paramyotonia Congenita. Sequencing of CLCN1 in all affected individuals also revealed the presence of a mutation known to cause Myotonia Congenita in exon 8, c.938C>T; p.Ala313Val in the severely affected individuals. This mutation was absent in the mildly affected individuals. In this pedigree the phenotypic variability is therefore most likely due to a double hit of two myotonia-causing mutations in different genes. This suggests that it is important to sequence all myotonia genes in pedigrees with marked phenotypic variability.